Cruel and unusual eaudiobook - Cornwell, Patricia (Kay Scarpetta, 1993)
When an executed murderer's fingerprints turn up at a new crime scene, Kay Scarpetta investigates. Prepare for the kind of riveting suspense this best-selling author delivers so well.